2008
DOI: 10.1590/s0103-84782008000800009
|View full text |Cite
|
Sign up to set email alerts
|

Boron and calcium sprayed on 'Fuyu' persimmon tree prevent skin cracks, groove and browning of fruit during cold storage

Abstract: IIIBoron and calcium sprayed on 'Fuyu' persimmon tree prevent skin cracks, groove and browning of fruit during cold storage

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In the case of the persimmons exposed to T1, softening could have been the consequence of the susceptibility of the fruit of persimmons 'Fuyu' to low temperatures in general, as suggested by other studies (Örvar et al, 2000). For each species, variety and organ, there is a combination of binomial time and temperature for which there is an associated increase in the content proteins involved in cold tolerance such as LEAs (late embryogenesis accumulated proteins), HSPs and molecules such sorbitol (Ferri et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the persimmons exposed to T1, softening could have been the consequence of the susceptibility of the fruit of persimmons 'Fuyu' to low temperatures in general, as suggested by other studies (Örvar et al, 2000). For each species, variety and organ, there is a combination of binomial time and temperature for which there is an associated increase in the content proteins involved in cold tolerance such as LEAs (late embryogenesis accumulated proteins), HSPs and molecules such sorbitol (Ferri et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, B applied alone or in combination with Ca did reduce russeting in tomato [119,124]. Several studies have reported decreased microcracking of fruit following applications of B, with or without Ca [187][188][189][190]. Since the initial steps in fruit cracking (macrocracking) and russeting would seem to be the same, in that both processes first require cuticular microcracking [191], it would not seem unlikely that applications of B will also decrease microcracking and russeting.…”
Section: Foliar Sprays Of Fertilizers and Other Compoundsmentioning
confidence: 96%
“…The calcium nitrate, calcium chloride and boron application decrease skin cracking in fruit of 'Fuyu' cultivar. The effect of boron is additive when is used in successive years (Ferri et al 2008).…”
Section: Rainfallmentioning
confidence: 99%